Factors associated with insufficient awareness of breast cancer among women in Northern and Eastern China: a case–control study. Issue 2 (20th February 2018) - Liu, Li-Yuan; Wang, Yong-Jiu; Wang, Fei; Yu, Li-Xiang; Xiang, Yu-Juan; Zhou, Fei; Li, Liang; Zhang, Qiang; Fu, Qin-Ye; Ma, Zhong-Bing; Gao, De-Zong; Li, Yu-Yang; et al.
Abstract : Objectives: To investigate the awareness and knowledge level of breast cancer among Chinese participants. Design: Case–control study. Settings: This study was based on the database of the minister-affiliated hospital key project of the Ministry of Health of the People's Republic of China that included 21 Chinese hospitals between April 2012 and April 2013. Participants: Matched study was designed among 2978 participants with Han ethnicity aged between 25 and 70. Primary and secondary outcome measures: Student's t-test, Pearson's χ 2 test, reliability analysis, exploratory factor analysis, and univariate and multivariate logistic regression analyses were performed to know the level of breast cancer knowledge and find the breast cancer awareness-associated factors. Results: 80.0% (2383/2978) of the participants had poor awareness level of breast cancer. In-depth knowledge of breast cancer such as early symptoms and risk factors was poorly found among them. Television broadcast and relatives or friends with breast cancers were the main sources of information about breast cancer. Of all participants, 72.8% (2167/2978) had heard about breast cancer as a frequent cancer affecting women, and 63.3% (1884/2978) knew that family history of breast cancer was a risk factor for breast cancer. Over half of them were aware that a breast lump could be a symptom of breast cancer. Multivariate analysis identified the following variables that predicted awareness of breast cancer: young age (OR=0.843, 95% CI 0.740 to 0.961), occupation (agricultural worker) (OR=12.831, 95% CI 6.998 to 23.523), high household social status (OR=0.644, 95% CI 0.531 to 0.780), breast hyperplasia history (OR=1.684, 95% CI 1.273 to 2.228), high behavioural prevention score (OR=4.407, 95% CI 3.433 to 5.657). Conclusion: Most women were aware of breast cancer as a disease, but their in-depth knowledge of it was poor. More publicity and education programmes to increase breast cancer awareness are necessary and urgent, especially for the ageing women and agricultural workers.